The Effect of Polymer Structures on Complete Degradation: A First‐Principles Study. Issue 6 (19th June 2018) - Zhu, Yu; Zhang, Depeng; Zhang, Zhanwen; Wang, Zhigang
Abstract: The widespread application of hydrocarbon polymer materials has spurred an increasing interest in the study of their dissociation mechanism, which is related to key issues such as environmental protection. In this work, the last‐step dissociation characteristics of carbon chain polymers were investigated. By using density functional theory, we considered all possible structures, including three typical normal linkage polymers and four typical abnormal linkage ones. In these structures, it can be found that the energy barrier required for the complete degradation of chain‐end saturated and unsaturated polymers are in the range of 3.42 to 4.78 eV and 0.35 to 1.31 eV, respectively. It shows that the unsaturated polymer is easier to degrade. Interestingly, as for three linkages of the polymer, the calculated results further suggest that the energy barrier of head‐to‐head, head‐to‐tail, and tail‐to‐tail linkages of the polymer dissociating to produce the monomer increase, no matter if the chain‐end is saturated or not. Therefore, we form a regular understanding of how to achieve the complete degradation of the polymer. In addition, analyses of the bond characteristics and electronic structures agree with the results of the energy barrier measurements. Meanwhile, the spin population analysis presents an obvious net spin transfer process in depolymerization reactions. We hope that the current results can provide a basic insight into polymer degradation. Abstract : Heads or tails? The energy barrier required for the complete degradation of three linkages (Head‐to‐Head, Head‐to‐Tail, and Tail‐to‐Tail) of chain‐end saturated and unsaturated poly‐α‐methylstyrene dimers is investigated (see picture).